The Effect of Resistance Band Training on Improving Basic Volleyball Techniques in Students Living in the Dogiyai Dormitory in Jayapura City - Darius Yobee; Miftah Fariz Prima Putra; Sulthan Hadist Ismaiedh Cukarso (Universitas Negeri Semarang, 2025)
Volleyball requires mastery of basic techniques such as serving, passing, setting, smashing, and blocking. However, many players on the field have difficulty mastering these skills due to monotonous training methods. This study used a quantitative approach with a one-group pretest-posttest experimental design. The sample consisted of 40 students from the Dogiyai dormitory in Jayapura City who were selected using purposive sampling. The resistance band training program was implemented for six weeks with a frequency of three times per week, including serving, passing, setting, and smashing exercises. Data were obtained through a basic volleyball skills test, then analyzed using normality tests, homogeneity tests, and paired sample t-tests with the help of SPSS 22.0. The results showed an increase in the average score from 15.60 in the pretest to 17.75 in the posttest with a difference of 2.15 points. Normality and homogeneity tests showed that the data were normally distributed and homogeneous. The results of the paired sample t-test showed a significance value of 0.000 <0.05, which means there was a significant difference between the pretest and posttest. The use of resistance bands significantly improved basic volleyball technical skills among students at the Dogiyai dormitory in Jayapura City. These findings provide practical insights for coaches and educational institutions in designing more varied, effective, and efficient training methods.